CARBON EMISSION DISCLOSURE IN INDONESIAN PLANTATION COMPANIES: EFFECTS OF ENVIRONMENTAL MANAGEMENT SYSTEMS, ENVIRONMENTAL AND FINANCIAL PERFORMANCE - Anggita Renata Sari; Andri Juansya (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
This study aims to evaluate the factors influencing carbon emission disclosure in plantation companies in Indonesia. The research employs a quantitative method, utilizing secondary data from annual reports, financial statements, and sustainability reports of plantation companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2022. Data analysis is conducted using purposive sampling, resulting in a sample of 25 companies. The panel data analysis model applied is the Common Effect Model (CEM) after undergoing the Chow test. The results indicate that environmental management systems (EMS) have a significant negative effect, environmental performance has a positive and significant effect, while financial performance does not have a significant effect on carbon emission disclosure. These findings highlight the importance of environmental performance in encouraging transparency, while the implementation of EMS does not necessarily lead to higher disclosure levels. This study contributes to understanding the determinants of carbon emission disclosure in Indonesia's plantation sector and provides insights for policymakers and companies in improving environmental transparency and sustainability practices.